Izkušnje pravnice z uporabo družbenega omrežja - Ahlin Doljak, Sara (Podjetje in delo, 2024)
Social networks have become an important part of both professional and personal life, enabling individuals to connect, communicate, and exchange information on a global level. Lawyers use social networks to increase their visibility, enhance their expertise, and disseminate knowledge and services. The author, facing challenges due to multiple sclerosis, highlights how social networking has enabled her to continue her professional work and improve her communication and networking in academic and business environments. A prerequisite for effective use of social networks is appropriate IT infrastructure and knowledge to use various platforms. Social networks present drawbacks such as false representation and potential social media addiction, but they can also offer a wide range of benefits, including expanding professional networks, offering services, and improving learning and teaching. Based on these findings, the author recommends that lawyers use social networks to enhance their professional paths through continuous education, offering their services, and exchanging experiences and knowledge with other professionals.